A Cause of Communication Failure in Managing Industrialized Building System (IBS) Projects: A Perspective View from Project Managers - Ahmad Pozin, Mohd Affendi; Mohd Nawi, Mohd Nasrun; Lee, Angela; Yaakob, Mazri; Hanafi, Mohd Hanizun (IJTech, 2018)
An effective communication process is an important element in distributing information to various project teams. The previous study demonstrates the importance of communication in the project management process in order to encourage project delivery processes successfully. Unfortunately, the issue of communication still dominates Industrialization Building System (IBS) because the project development process are still based on traditional methods. This research aims to explore the cause of communication challenges between construction players in managing IBS projects. The research methodology implemented for this paper was a semistructured interview approach used to investigate the communication problem. Five experienced project managers were chosen from across the industry. The findings of this study are valuable for improving the communication level of project teams, which will indirectly increase the level of the IBS project delivery process and strengthen team integration on IBS projects in Malaysia.